Long-term cycle stability of metal hydride-graphite composites. (14th December 2015) - Dieterich, Mila; Pohlmann, Carsten; Bürger, Inga; Linder, Marc; Röntzsch, Lars
Abstract: Recently, metal hydride composites (MHC) have been proposed which consist of a hydride forming metal alloy and a highly heat conduction secondary phase such as expanded natural graphite (ENG) in order to improve the thermal conductivity of metal hydride powder beds. However, only little data is available in the literature on the effects of extensive cycling on technically relevant properties of MHC. In this paper, hydrogenation characteristics, thermal conductivity and geometrical stability of Hydralloy ® C5-based MHC were thoroughly investigated over 1000 cycles. The obtained results suggest that the MHC under study did not significantly alter their hydrogen uptake characteristics throughout cycling, despite the fact that their thermal conductivity decreased during the first 250 cycles but remained constant thereafter. Although the cylindrical MHC maintained their geometrical stability, radial cracks were detected after cycling. Based on these results, MHC are suitable for high-dynamic applications such as hydrogen storage or thermochemical devices. Graphical abstract: Highlights: Metal hydride composites show constant temperature responses throughout 1000 cycles. The thermal conductivity first decreased but was constant afterwards (10–15 Wm −1 K −1 ). Metal hydride composites exhibit high mechanical integrity even after 1000 cycles.